THE CREATION OF ELIM-AI - Hancock-Parmer, Michael (Journal of history, 2017)
This article presents the events of the Kazakh-Dzungarian wars of the first third of the 18th century and the most important tragic years of the Aktaban Shubyryndy. An attempt was made to disclose these difficult events «Aktaban Shuburyndy» through the research of the famous scientist Mukhamedzhan Tynyshpaev and oral folk art the Kazakh people, namely the song «Elim Ai». The author examines in detail the history of the appearance of the song «Elim Ai», draws attention to the fact that the text of the song was published in issue 52 of the journal «Kazak» in 1914. A year later the text was again published in the collection «Terme» in 1915 in Orenburg. The author tried to analyze the text of music and music.